2015
DOI: 10.1002/chem.201501678
|View full text |Cite
|
Sign up to set email alerts
|

Host–Guest‐Mediated DNA Templation of Polycationic Supramolecules for Hierarchical Nanocondensation and the Delivery of Gene Material

Abstract: Only a few examples of monodisperse molecular entities that can compact exogenous nucleic acids into nanocomplexes, protect the cargo from the biological environment, facilitate cell internalization, and promote safe transfection have been reported up to date. Although these species open new venues for fundamental studies on the structural requirements that govern the intervening processes and their application in nonviral gene-vector design, the synthesis of these moieties generally requires a relatively soph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 80 publications
1
30
0
Order By: Relevance
“…We recently demonstrated that the propensity of non‐amphiphilic CD‐based molecular nanoparticle entities to integrate pDNA‐templated bilayer arrangements could be programmed by supramolecular preorganization into dimers (Figure B), thereby dramatically enhancing the transfection efficiency in vitro compared to the monomer by more than three orders of magnitude . High transgene expression levels, comparable to those obtained with paCDs, were achieved in the lung and the liver in vivo in mice.…”
Section: Introductionmentioning
confidence: 94%
“…We recently demonstrated that the propensity of non‐amphiphilic CD‐based molecular nanoparticle entities to integrate pDNA‐templated bilayer arrangements could be programmed by supramolecular preorganization into dimers (Figure B), thereby dramatically enhancing the transfection efficiency in vitro compared to the monomer by more than three orders of magnitude . High transgene expression levels, comparable to those obtained with paCDs, were achieved in the lung and the liver in vivo in mice.…”
Section: Introductionmentioning
confidence: 94%
“…Amine-functionalized CD 1 is av ersatile scaffold, which has been used for the design of fluorescent sensors, [10,45] synthetic receptors, [46] investigated as ap recursor to forming glycoclusters, [47] controlling protein self-assembly, [48] DNA transfection, [49] and as an inhibitor of anthraxl ethal toxin. [50][51][52][53] In these examples, the amine groups of 1 were either per-functionalized, or monofunctionalized nonselectively with desired reagents.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest for our goals is the fact that βCD can form inclusion complexes with docetaxel and that the incorporation of βCD in nanomaterials can be used to impart high DTX loading capabilities (Zhao and Astruc, 2012; Wang et al, 2016). Although canonic βCD exhibit some renal toxicity after parenteral administration, related to its greater ability to interact with cellular lipids leading to cell-membrane damage, toxicity is greatly reduced after chemical modification (Stella and He, 2008; Gallego-Yerga et al, 2015a). Indeed, amphiphilic βCD derivatives showed no apparent toxicity in animal models (Mendez-Ardoy et al, 2011; Aranda et al, 2013; Gallego-Yerga et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…Although canonic βCD exhibit some renal toxicity after parenteral administration, related to its greater ability to interact with cellular lipids leading to cell-membrane damage, toxicity is greatly reduced after chemical modification (Stella and He, 2008; Gallego-Yerga et al, 2015a). Indeed, amphiphilic βCD derivatives showed no apparent toxicity in animal models (Mendez-Ardoy et al, 2011; Aranda et al, 2013; Gallego-Yerga et al, 2015a). …”
Section: Introductionmentioning
confidence: 99%